Families in the Intensive Care Unit A Guide to Understanding, Engaging, and Supporting at the Bedside (Springer International Publishing, 2018)
This text is one of the first comprehensive resources on understanding and working with families in the intensive care unit. The text provides a conceptual overview of the Family ICU Syndrome, a constellation of physical morbidity, psychopathology, cognitive deficits, and conflict. Outlining its mechanisms, the book presents a guide to combating the syndrome with an interdisciplinary team. The text represents the full array of the interdisciplinary team by also spotlighting administrative considerations for health care management and approaches to training different members of the health care team. Family voices are featured prominently in the text as well. The book also addresses the complete trajectory of needs of care, including survivorship and end-of-life care. Written by experts in the field, Families in the Intensive Care Unit: A Guide to Understanding, Engaging and Supporting at the Bedside is a state-of-the-art reference for all clinicians who work with families in the ICU.